To change or not to change – how primary school teachers speak about stability and change - Pehkonen, Leila (NOMAD Nordic Studies in Mathematics Education, 2007)
Changing mathematics education and teachers has proved to be difficult. In this case study the matter has been turned upside down. The purpose is to approach the question of change from the perspective of stability. In this paper I will discuss how primary school teachers speak about stability, and – in this connection – about changes in mathematics teaching. The data consists of semi-structured interviews of nine primary school teachers and is analyzed qualitatively. The findings suggest complex relationships between the need for continuity and the desire for changes.